Pengaruh Teknik Relaksasi Genggam Jari Terhadap Skala Nyeri Haid Pada Remaja Putri Di SMK Tunas Bangsa (DECES) Jurusan Keperawatan Tahun 2023 - Zhalva Camila Laila Rozni; Susaldi Susaldi; Agus Purnama (Inovasi Kesehatan Global, 2024)
Menstrual pain, also known as dysmenorrhea, is one of the menstrual disorders most often experienced by women. Dysmenorrhea is caused by pain during menstruation which is felt in the lower abdomen or Michael's square area. This pain can be felt before, during and the end of the menstrual cycle and can be colicky or continuous. The finger hold relaxation technique is a very simple and easy method for anyone to do in contact with the fingers and the flow of energy in our body so that it can provide a feeling of relaxation, comfort and reduce pain. The aim of this research is to determine the effect of finger-hold relaxation techniques on the scale of menstrual pain in young women at SMK Tunas Bangsa (DECES) majoring in nursing in 2023. The method used is quantitative research with a pre-experimental research design in the form of One Group Pretest Posttest Design. The sampling technique used in the research was the Stratified Random Sampling method with a total research sample of 36 female students. Data analysis using the Wilcoxon Sign Rank test obtained results with a significant p-value of 0.000 (<0.05). The conclusion of the research is that the finger-hold relaxation technique has an effect on the scale of menstrual pain in young women at Tunas Bangsa Vocational School (DECES) majoring in nursing.